1984
DOI: 10.1002/1097-0142(19841101)54:9<1860::aid-cncr2820540916>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonepithelial tumors of the nasal cavity, paranasal sinuses, and nasopharynx. A clinicopathologic study. XIII: Meningiomas

Abstract: Twelve cases of meningiomas involving the nasal cavity and paranasal sinuses are reported. Meningiomas only rarely involve the upper respiratory tract; these 12 cases were found among the 566,000 surgical pathology cases that have been studied in this laboratory. In this series, five meningiomas probably arose in the cranial cavity and secondarily extended into the nasal cavity and paranasal sinuses. Because radiographs demonstrated hyperostosis or bone destruction, three other tumors could have involved the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Meningiomas constitute between 20 and 36 % of intracranial neoplasms [76,77], but primary extracranial (ectopic, extracalvarial) meningiomas account for only about 2 % of all meningiomas, with meningiomas of the sinonasal tract comprising \0.1 % of non-epithelial neoplasms [78][79][80]. Extracranial direct extension into the sinonasal tract of meningiomas is much more likely than a primary, ectopic tumor, and thus, by current consensus, a primary diagnosis should not be rendered when there is a detectable intracranial mass or ''dural enhancement'' by imaging [79][80][81].…”
Section: Meningiomamentioning
confidence: 99%
See 1 more Smart Citation
“…Meningiomas constitute between 20 and 36 % of intracranial neoplasms [76,77], but primary extracranial (ectopic, extracalvarial) meningiomas account for only about 2 % of all meningiomas, with meningiomas of the sinonasal tract comprising \0.1 % of non-epithelial neoplasms [78][79][80]. Extracranial direct extension into the sinonasal tract of meningiomas is much more likely than a primary, ectopic tumor, and thus, by current consensus, a primary diagnosis should not be rendered when there is a detectable intracranial mass or ''dural enhancement'' by imaging [79][80][81].…”
Section: Meningiomamentioning
confidence: 99%
“…While radiation exposure and sex hormones are known to play a role in meningioma development [76,78,80], these factors are unproven in sinonasal tract tumors. There are three grades (as defined by the World Health Organization) and 15 recognized histologic types [76].…”
Section: Meningiomamentioning
confidence: 99%
“…56 Chordomas arising from the most rostral notochord extension in the dorsum sellae present as sellar 96 or parasellar tumors. Those arising from the most ventral aspect of the clivus can present as nasopharyngeal chordomas, 16,42,75,80,108 whereas those associated with the body and dorsal aspect of the clivus manifest as sphenooccipital or petrosal lesions. Chordomas related to the lower clivus will present at the ventral portion of the foramen magnum.…”
mentioning
confidence: 99%
“…However, primary extracranial (ectopic, extra calvarial) meningiomas of the nasal cavity, paranasal sinuses, and nasopharynx (here in after referred to collectively as the sinonasal tract) are rare. The largest study to date is of 12 cases reported by Perzin et al [18] While a degree of controversy continues to exist around the exact origin of sinonasal tract meningiomas, it seems generally accepted that primary extracranial meningiomas do occur. Histologically, meningiomas of the sinonasal tract are identical to their intracranial counterparts, although diagnostic difficulties are frequently encountered in the differential diagnosis with carcinoma, melanoma, and olfactory neuroblastoma resulting from the rarity of meningiomas in this location.…”
Section: Discussionmentioning
confidence: 99%